VALORIZATION OF TOMATO AND CABBAGE WASTE FOR BIOHYDROGEN AND FERTILIZER PRODUCTION THROUGH TRICHODERMA-AIDED DARK FERMENTATION - I Wayan Budiarsa Suyasa; Gede Adi Wiguna Sudiartha; I Gusti Agung Gede Bawa; Huy Thanh Vo; Shingo Nakamura (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
Aims: The current study aimed to investigate the feasibility of biohydrogen production from tomato and cabbage waste through dark fermentation with Trichoderma spp. supplementation to enhance substrate degradation. Methodology and results: Laboratory-scale anaerobic reactors with five different Trichoderma concentrations (0.0, 2.5, 5.0, 7.5, and 10.0 g) were operated at room temperature for 112 days, during which hydrogen production, glucose consumption, pH, and temperature were continuously monitored. The highest cumulative hydrogen yield was observed in the treatment with 2.5 g of Trichoderma, achieving 44.65 mmol H₂/mol glucose, which is three times greater than the control. Correlation analysis revealed that optimal biohydrogen production was associated with extended incubation periods, elevated temperatures, and lower pH levels (below 6.0); however, increased concentrations of Trichoderma did not consistently enhance hydrogen yield. The liquid digestate from the best-performing reactor was applied as a biofertilizer for chilli seedlings. The 5% digestate treatment significantly promoted plant height and leaf growth compared to the control, suggesting the beneficial effects of bioactive compounds produced by Trichoderma. Conclusion, significance, and impact study: Reactor supplemented with 2.5 grams of Trichoderma exhibited the highest biohydrogen production, and a 5% digestate concentration enhanced the growth of chilli seedlings. This study demonstrates the dual potential of agricultural waste valorisation, producing renewable energy and supporting sustainable agriculture, highlighting the promising role of microbial-aided fermentation and biofertilizer applications in circular bioeconomy models.